Learning Analysis of the Long Jump Material Using the Playing Method for Junior High School Students - Rubi Yatno (Universitas Serambi Mekkah, 2022)
This study aims to determine how the learning outcomes of the squat stylelong jump using the play method in class VIII students of State Junior HighSchool 1 Kuburaya. The form of research used in this research isexperimental research with two stages consisting of planning,implementation, observation, reflection, and conclusion. The subjects in thisstudy were Class VIII students, totaling 35 students. The results ofimproving soccer passing learning using the inside of the foot are obtainedby comparing the observation value with the initial test before the actionknown as